(untitled) (Research, Society and Development, 2022)
Introduction: From birth, breastfeeding and mother-infant interaction can modulate the child’s behavioral state, influencing their psychological learning development and, consequently, their future food choices. General Objective: to understand the causes that lead children to develop food selectivity, factors that contribute to it and how we can help children through nutritional guidance and education. Methodology: This research will be a literature review and an initial search was carried out in the databases from journals and scientific articles in Lilacs, Scielo and Pubmed, Google academic, Scienc direct, Mediline and CAPES journals, Virtual Health Library and books. Results and Discussion: Nutritional education is the preventive approach to children’s food selectivity. It aims to develop appropriate attitudes towards food, considering so many cognitive, emotional and behavioral aspects. Conclusion: From the development of this study, it was possible to understand that the eating habits of selective children is formed by a bland, monotonous, repetitive diet and generally different from the family’s diet, they are children who eat only at home and when they go out to a certain place has to take their own food, as they end up not accepting other types of food that they are not used to.